Comparative study on nutrient composition and antioxidant capacity of potato based on geographical and climatic factors. (April 2022) - Zhang, Bing; Murtaza, Ayesha; Iqbal, Aamir; Zhang, Jiao; Bai, Tingting; Ma, Wanlu; Xu, Xiaoyun; Pan, Siyi; Hu, Wanfeng
Abstract: Potatoes are consumed in the human diet, but the environmental effects on the nutrient content of their tubers are not known. Five potato varieties from China (Chongqing, Dingxi, Qiqihar, Enshi, and Ulanqab) were selected to compare their nutritional components and antioxidant capacity and to explore the correlation between nutrition and local rainfall, humidity, temperature, and light time. The results indicated the Qiqihar cultivar presents significantly higher antioxidant capacity, and has the most elevated protein and soluble sugar contents. The total phenol (TPC) (325.07 μg/g) and carotenoid contents (54.93 μg/100g) of the Ulanqab cultivar were the highest. The Dingxi cultivar reveals the highest total flavonoids (TFC) (168.94 μg/g), K, Mg, and P contents. The ascorbic acid content (26.09 mg/100g) was the highest in the Chongqing cultivar, and the contents of starch, Ca, total acid, and water were also prominent. The amino acid content (7.350%) in the Enshi cultivar is higher. It was found that soluble sugar was significantly correlated with humidity, temperature, and light time; carotenoids were affected considerably by rainfall; ascorbic acid has a strong correlation with temperature; TPC was moderately associated with humidity and light time. To summarize, tubers' nutrient composition and antioxidant capacity vary with geographical location and climate of origin. This study will help provide a theoretical basis for selecting geographical areas for potato planting and exploring the complex interactive factors between environment and vegetable attributes. Highlights: Potato varieties from five major production areas in China were studied. The antioxidant capacity of varieties in Qiqihar and Dingxi is more prominent. Nutrient composition and antioxidant capacity of tubers are influenced by geographical location and climate of origin. Correlation analysis was used to investigate the correlation between climatic conditions and nutrient content.